O la capra o i cavoli La biosfera, l'economia e il futuro da inventare - Bellanca, Nicolò (Studi e saggi, 2020)
We cannot have the goat and the cabbages together. We cannot jointly achieve the preservation of the planet, economic growth and the improvement of individual and collective well-being. Climate and energy issues are not a crisis, and even an emergency, but a historic passage that we must face by committing ourselves to grasping the exact terms of the difficulties and dangers. We must give up part of our lifestyle, reducing population and economy as quickly, but also the less traumatically possible. We must abandon the criterion of efficiency for that of sufficiency. We need to stop thinking about what we could do more and start thinking about what we can do less.